Analysis Of Sugar Planning In PG Mojo Sragen - Mayang Puspitasari, Diah; Dewi Lestari, Retna; Rahyunanto, Setyo (LPPM Universitas Duta Bangsa Surakarta, 2024)
This study aims to analyze the planning of sugar production capacity is efficient or not in PG Mojo Sragen. Although the level of sugar production capacity in a particular year still exceeds capacity and also lacks capacity. The production capacity planning analyzed includes the available capacity and the required capacity of each station, namely the refining station, evaporation, cooking, turning, Waste Water Treatment Plant (WWTP), and stamfloor (sugar packaging place). The analysis method used is RCCP (Rought Cut Capacity Planning). The results showed that the comparison of the efficiency of each workstation which was said to be inefficient was found at the evaporation workstation, WWTP, and stamfloor. The three stations have lower available capacity compared to the higher required capacity. This research is expected to provide insight for PG Mojo Sragen to increase available capacity through better alternatives.